28-day inhalation toxicity of 3-methoxybutyl chloroformate in rats. (2018) - Kim, Hyeon-Yeong; Cho, Eun-Sang
Graphical abstract: Highlights: 3-MBCF up to 6 ppm induced mortality in 28-day inhalation study of rats. The NOAEL of 3-MBCF in 28 day inhalation toxicity study, was less than 3 ppm. 3-MBCF under 12 ppm did not induce micronucleus formation in the bone marrow of rats. Abstract: The 28-day repeated inhalation study was applied for hazard assessment of 3-methoxybutyl chloroformate (3-MBCF) in Sprague Dawley rats. Groups of five rats per sex were exposed 6 h/day, 5 days per week for 4 weeks to test substance concentration (ranging from 3 to 12 ppm) using a whole-body exposure system. At the terminal sacrifice, following blood collection and gross pathological examination, organ weights were determined and fixed organs were examined. The micronucleus test was performed using bone marrow cells. Exposure of 3-MBCF induced mortality at concentrations above 6 ppm. Decreases in body weight and food intake, hematologic alterations, organ weight changes, and gross and microscopic findings were seen even at the lowest concentrations of 3 ppm. Histopathology revealed principal test substance exposure correlated with lesions in the respiratory tract in both male and female rats above 3 ppm. Groups of male rats exposed above 6 ppm show microscopic lesions in spleens, livers, testes and epididymides; however, the micronucleated polychromatic erythrocytes frequency in bone marrow cells was not changed. Based on histopathology of the respiratory tract and other organs, the no observed adverse effect level (NOAEL) of 3-MBCF in the present study was less than 3 ppm.